Age-related penetrance of hereditary atypical hemolytic uremic syndrome - Sullivan, Maren; Rybicki, Lisa A.; Winter, Aurelia; Hoffmann, Michael M; Reiermann, Stefanie; Linke, Hannah; Arbeiter, Klaus; Patzer, Ludwig; Budde, Klemens; Hoppe, Bernd; Zeier, Martin; Lhotta, Karl; et al. (Annals of human genetics, 2011)
Hereditary atypical hemolytic uremic syndrome (aHUS), a dramatic disease frequently leading to dialysis, is associated with germline mutations of the CFH, CD46, or CFI genes. After identification of the mutation in an affected aHUS patient, single-site gene testing of relatives is the preventive care perspective. However, clinical data for family counselling are scarce. From the German-Speaking-Countries-aHUS-Registry, 33 index patients with mutations were approached for permission to offer relatives screening for their family-specific mutations and to obtain demographic and clinical data. Mutation screening was performed using direct sequencing. Age-adjusted penetrance of aHUS was calculated for each gene in index cases and in mutation-positive relatives. Sixty-one relatives comprising 41 parents and 20 other relatives were enrolled and mutations detected in 31/61. In total, 40 research participants had germline mutations in CFH, 19 in CD46 and in 6 CFI. Penetrance at age 40 was markedly reduced in mutation-positive relatives compared to index patients overall with 10% versus 67% (P < 0.001); 6% vs. 67% (P < 0.001) in CFH mutation carriers and 21% vs. 70% (P= 0.003) in CD46 mutation carriers. Age-adjusted penetrance for hereditary aHUS is important to understand the disease, and if replicated in the future, for genetic counselling.